Variables que contribuyen a la consolidación de la red de centros urbanos de la ciudad región, tren de cercanías-sabana de occidente (2013)
The territorial planning generates a direct relationship with the Mobility Systems from one regional perspective: those infrastructure projects are considered to be a part of the structuring components in the makeup of the Cities Networks. Hence the conditions of those schemes in the region, Bogotá-Cundinamarca, are in the process of changing with the implementation of new transportation systems (like the case of the Suburban Train).